الأبعاد الفنية والتربوية في قصص الأطفال الإلكترونية (موقع قصص أطفال قبل النوم أنموذجا) - كوثر بحري; منى مروة; لميس بن خليفة; ريحاب بريبش; آية الرحمان عزوز (University of Eloued جامعة الوادي, 2024)
تهدف هذه "الأبعاد الفنية والتربوية في قصص الأطفال الإلكترونية (موقع قصص أطفال قبل النوم)، إلى استنطاق الأبعاد التربوية والتعليمية من القصص الإلكترونية الموجهة للطفل، كما تعتبر قصص الأطفال الإلكترونية وسيلة من وسائل السرد تحتويها صور وفيديوهات وصوت الراوي، تهدف إلى فعالية وتبسيط أحداث القصة لإيصال المعلومة للقارئ الطفل تحت إطار تشويقي فعال. فالطفل سهل التلقي والتقليد من القصص الإلكترونية، فهذه الوسائط تلعب دوراً كبيراََ في بناء أو هدم الطفل في عصرنا عصر العولمة والتكنولوجيا اليوم. ولإثبات هذه الدراسة اعتمدنا على مناهج مختلفة (البنيوي، السيميائي) وما يلحقه من وصف وتحليل، بقصد القدرة على تحليل وتفكيك بنية القصة، كما حدثت دراسة الموضوع وفق خطة تتكون من مدخل وفصلين وخاتمة، كان الفصل الأول معنوناً ب: الأبعاد الفنية في قصص الأطفال الإلكترونية المختارة (الكتكوت ذو الريشة الحمراء والصدقة)، أما الفصل الثاني موسوماً ب: بنية الشخصيات في القصص الإلكترونية المختارة (الكتكوت ذو الريشة الحمراء والصدقة) واكتمل البحث بخاتمة كانت حصيلة لأهم نتائج الدراسة. This "artistic and pedagogical dimensions of e-children's stories (bedtime children's stories site), aims to derive educational and educational dimensions from child-oriented e-stories. E-children's stories are also seen as a means of narrating images, videos and narrators' voices, aiming at the effectiveness and streamlining of story events to communicate information to the child reader under an effective promotional framework. Children are easy to receive and imitate from electronic stories. These media play a major role in building or demolishing children in today's era of globalization and technology. To demonstrate this study, we relied on different approaches (structural, semitic) and the subsequent description and analysis, with a view to being able to analyses and dismantle the structure of the story. The study also took place according to a plan consisting of an introduction, chapters and a conclusion. Chapter I was entitled: Technical dimensions of selected children's electronic stories (red-feathered chick and honesty), and chapter II marked with: The structure of the characters in the selected electronic stories (red-feathered chick and honesty) and the research was completed with a conclusion that was the result of the most important results of the study
دراسات أدبية
Keywords: قصص، الأطفال، الأبعاد، الفنية- التعليمية، الوسائط، البنية; Stories; Children; Dimensions; Technical-Educational; Media; Structure